Responsiveness of Residential Natural Gas Demand to Elderly, Urban Population and Density: Evidence from Organization for Economic Co-operation and Development Countries - Malzi, Mohamed Jaouad; Ettahir, Aziz; Hanchane, SaÃ¯d (International Journal of Energy Economics and Policy, 2019)
This paper empirically examines per capita residential natural gas demand using annual data for 29 OECD countries from 2005 to 2016. Earlier studies have focused on the effect of price and income to estimate natural gas demand elasticities, but most of them have neglected the demographic variables such as elderly population, population density and urbanization rate. The aim of this work is to include these attributes for modeling the demand function of natural gas. To address the problem of endogeneity, we use a dynamic panel system called Generalized Method of Moments (GMM) estimator. Our study presents the following main results; First, the increase of the urbanization rate leads to more per capita consumption of natural gas in the residential sector. Second, the ageing of the population decreases the use of per capita residential natural gas in OECD countries. Third, as population density increases, per capita residential natural gas consumption decreases. Keywords: Residential Gas Demand, Generalized Method of Moments, Population Characteristics and Consumption JEL Classifications: Q31, Q41, Q43 DOI: https://doi.org/10.32479/ijeep.7531